The Diversity and Ecological Role of Non-scleractinian Corals (Antipatharia and Alcyonacea) on Scleractinian Cold-Water Coral Mounds - De Clippele, Laurence Helene; Huvenne, Veerle A. I.; Molodtsova, Tina N.; Roberts, J. Murray (Frontiers in Marine Science, 2019)
Cold-water coral carbonate mounds, created by framework-building scleractinian corals, are also important habitats for non-scleractinian corals, whose ecology and role are understudied in deep-sea environments. This paper describes the diversity, ecology and role of non-scleractinian corals on scleractinian cold-water coral carbonate mounds in the Logachev Mound Province, Rockall Bank, NE Atlantic. In total ten non-scleractinian species were identified, which were mapped out along eight ROV video transects. Eight species were identified as black corals (three belonging to the family Schizopathidae, one each to the Leiopathidae, Cladopathidae and Antipathidae and two to an unknown family) and two as gorgonians (Isididae and Plexauridae). The most abundant species were Leiopathes sp. and Parantipathes sp 2. Areas with a high diversity of non-scleractinian corals are interpreted to offer sufficient food, weak inter-species competition and the presence of heterogeneous and hard settlement substrates. A difference in the density and occurrence of small vs. large colonies of Leiopathes sp. was also observed, which is likely related to a difference in the stability of the substrate they choose for settlement. Non-scleractinian corals, especially black corals, are an important habitat for crabs, crinoids and shrimps in the Logachev Mound Province. The carrier crab Paromola sp. was observed carrying the plexaurid Paramuricea sp. and a black coral species belonging to the genus Parantipathes, a behaviour believed to provide the crab with camouflage or potentially a defence mechanism against predators. More information on the ecophysiology of non-scleractinian corals and fine-scale local organic matter supply are needed to understand what drives differences in their spatial distribution and community structure.